Inovasi Media Digital Storytelling dalam Pembelajaran IPS untuk Meningkatkan Literasi Sosial Siswa - Treesly Y.N Adoe; Markus Sampe; Taty R Koroh; Vera R Bulu (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the effectiveness of Digital Storytelling media in improving students’ social literacy in Social Studies learning at SD Inpres Naikoten 1, Kupang. The study employed a quantitative approach using a quasi-experimental method with a Pretest–Posttest Control Group Design. The participants consisted of 64 fifth-grade students, comprising 32 students in the experimental class and 32 students in the control class. The experimental class received Social Studies instruction using Digital Storytelling media, while the control class received conventional instruction. Data were collected through social literacy tests, student activity observation sheets, student response questionnaires, and documentation. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, Independent Sample t-test, and Normalized Gain analysis. The results showed that the experimental class achieved a higher posttest mean score of 87.63 compared with 73.28 in the control class. The Independent Sample t-test produced a significance value of 0.000 (<0.05), indicating a significant difference between the two groups. Furthermore, the experimental class obtained an N-Gain score of 0.69, while the control class obtained 0.35. These findings indicate that Digital Storytelling is more effective than conventional learning in improving students’ social literacy. The integration of narration, images, animation, video, music, and reflective questions creates a more contextual, interactive, and meaningful learning experience. Digital Storytelling also encourages students to analyze social problems, communicate ideas, collaborate, demonstrate empathy, and formulate responsible solutions. Therefore, Digital Storytelling can be considered an effective and innovative learning medium for supporting Social Studies learning and strengthening elementary school students’ social literacy in the context of 21st-century education and the implementation of the Merdeka Curriculum.